Factors Determining the Technical Efficiency of Rural Households in Dak Lak Province of Vietnam - Niem, Le Duc (Journal of Development and Administrative Studies, 2018)
Most agricultural programs generally aim at helping poor households.They become the cornerstone to enhance some self-employed activities. Thus, identifying factors which are significant to extend their existing skills and income-generating opportunities is considered an important step in designing a program to improve performance of rural households. This paper derives some statistically significant determinants of the technical efficiency of rural households and gives some implications for poverty reduction efforts in rural areas of Ea H’leo district, Daklak province. The Journal of Development and Administrative Studies (JODAS) Vol. 24 (1-2), pp. 17-24